Growth Dynamics and Production of Kara Oncet Bean (Ficia Faba L.) Through Plant Growth Analysis Approach To Get Optimum Planting Distance - Aditiameri Aditiameri (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
Setting the spacing with a specific density allows each plant to grow well. Spacing will affect the density and efficiency of light use and competition between plants in the use of water and nutrients to affect crop production. At low densities, plants compete less with other plants so that individual plant performances are better. Conversely, at high densities, the competition between plants for light, water, and nutrients is getting tighter so that plant growth can be stunted. Each kara oncet bean cultivar responds differently to different plant density levels. The experiment was conducted in farmers' rice fields in Lembang with Andosol soil. The altitude is 1500 m above sea level. Cangar and Bromo kara oncet bean cultivars with populations of 83,333 plants per ha, 66,667 plants per ha, and 55,556 per ha were studied using factorial block design with four replications. The response surface methodology and snugness test responses to find the highest population of each kara oncet bean cultivar. From the experimental results, it turns out that different plant populations cause differences in (ILD), (LTT), (LAB), and results. The optimum population to obtain the highest yield of two faba bean cultivars has not yet been determined. The components of plant organs that can be relied upon as a determinant of the yield of kara oncet beans are the number of pods per plant, the number of seeds per plant, and the weight of 25 dry seeds.